A Newly Discovered Edition of the English Palmerin D'oliva. (12th June 2020) - Sánchez-Martí, Jordi
Abstract: This note examines the fragments of the English Palmerin d'Oliva discovered in the library of Christ Church, Oxford, in 2017. First, it briefly discusses the course the Castilian Palmerín de Olivia followed on the Continent until it crossed to England, where Anthony Munday's translation appeared in 1588. After explaining how the fragments were located, their placement, nature and contents are described. The text in the Christ Church fragments is collated with the other editions of the English Palmerin d'Oliva . The ESTC conjecturally states that the newly discovered edition was printed c. 1600 by Thomas Creede and Bernard Alsop. This article, however, argues that the available textual, typographical and bibliographical evidence suggests that this edition must have been printed c. 1609 by Creede, without the participation of Alsop. Finally, note is taken of the presence on the pages of the handwriting of Henry Aldrich, the seventeenth-century dean of Christ Church.